Improvement of an Existing Racking System Safety Inspection Checklist for Warehouse Operations in the Food Industry - Airul Azhar, Nur Syamimie; Ahmad, Mohd Akhir; Sukadarin, Ezrin Hani; Najmi Ibrahim (Progress in Engineering Application and Technology, 2026)
The goal of this project is to overcome the drawbacks of manual paper-based inspection techniques by developing and testing a streamlined digital racking safety inspection checklist for warehouse operations. Conventional checklists frequently lead to incomplete documentation, subjective damage classification, and inconsistent assessments. The suggested digital checklist incorporates QR code access, structured inspection items, photo documentation, and automated reporting workflows. It was created using Microsoft 365 tools, including Microsoft Forms, SharePoint, and Power Automate. The System Usability Scale (SUS) was used to assess system usability in a descriptive developmental approach. In support of more efficient and proactive warehouse safety management, the results show that the digital checklist improves inspection clarity and data consistency, guaranteeing higher user satisfaction than the manual checklist.